Pengaruh Penerapan Media Digital Interaktif terhadap Penanaman Nilai-Nilai Keislaman pada Anak Usia Dini di Era Society 5.0 - Daulay, Hopman (Journal Education Innovation (JEI), 2025)
This study aims to examine the impact of using interactive digital media in teaching Islamic values to early childhood learners in the era of Society 5.0. The research employs a descriptive qualitative method, utilizing observation, interviews, and documentation for data collection. The findings indicate that the use of digital media—such as Islamic animated videos and educational applications—positively influences children's interest and understanding of Islamic values. Digital media can present Islamic content in an engaging and interactive way, aligned with the developmental characteristics of young children. However, several challenges remain, including limited access to technology, lack of parental support, and low digital literacy among educators. Therefore, ongoing teacher training and adequate infrastructure support are essential to ensure the effective and sustainable integration of digital media in early childhood education.